Syringic acid loaded chitosan nanoparticles mitigate glycation associated oxidative stress and inflammation in hyperglycaemic rat model - Andleeb Rasheed; Sairah Hafeez Kamran; Misbah Hameed; Farhan Siddique; Sumera Latif; Mehvish bibi; Roha Rizwan (Scientific Reports)
Abstract Syringic acid (SA), a phenolic compound, is found naturally in several plants, fruits, and vegetables and has numerous therapeutic attributes. The objective of the research was to investigate the possible impact of syringic acid nanoparticles (SANPs) on hyperglycemia, particularly in relation to advanced glycation end products, reactive oxygen species, and inflammation. SANPs were prepared by ionic gelation method and characterized. Rats were divided into 5 groups, normal control, high-fat and high-fructose diet (HFFD), HFFD + metformin (120 mg/kg), HFFD + SA (30 mg/kg) and HFFD + SANPs (15 mg/kg). Rats showed a remarkable decrease in body weight (↓31.61%) and fasting blood glucose levels (↓62.63%) in HFFD + SANPs group. The HbA1c decreased from 5.8 ± 0.05% in HFFD to 4.4 ± 0.12% in HFFD + SA and 4.1 ± 0.16% in HFFD + SANPs treatment groups. The administration of SANPs resulted in a considerable improvement (p < 0.001) in the activity of glyoxalase-1 (Glo1, 0.19 ± 0.003 U/mg protein), glyoxalase-2 (Glo2, 0.14 ± 0.002 U/mg protein) and hexokinase-2 (29.19 ± 2.24 ng/dL). There was a significant decrease (p < 0.001) in malondialdehyde (MDA) levels along with increased glutathione (GSH), superoxide-dismutase (SOD) and catalase activity. The in-silico analysis indicated potential binding affinities with hexokinase 2 (-5.4), IL-6 (-5.7), catalase (-5.8), MDA (-5.4) and GSH (-5.1). Furthermore, these interventions resulted in enhancements in the plasma concentrations of lipid profile components as well as improvements in liver function tests and expression of pro-inflammatory cytokines including IL-6, IL-8 and NF-κB. Utilization of SANPs holds promise as a therapeutic strategy for mitigating hyperglycemia.